Investigation of leachate recirculation effects in Istanbul Odayeri Sanitary Landfill - Ozkaya, B; Demir, A; Basturk, A; Bilgili, MS (MARCEL DEKKER INC, 2004)
Each day approximately 10,000t of municipal solid wastes (MSW) arc being produced in Metropolitan Municipality Area of Istanbul. These wastes are disposed at convenient sanitary landfills. MSWs on the European side are being disposed at Odayeri Sanitary Landfill and this study is carried out at this landfill. Approximately 1.5 ha of landfill area is selected as test area for leachate recirculation and the leachate is recirculated to the wells, which arc opened at 14 points, and have 18 m depth, 0.4 to diameter. This research presents a summary of findings from a full-scale sanitary landfill study conducted for the first time in Turkey. It also presents the results of the monitoring data obtained from the test area in Odayeri Sanitary Landfill. It attempts to quantify the effects of leachate recirculation in terms of various stabilization indicators, landfill gas (LEG) composition, leachate analysis, and landfill settlement.
Keywords: leachate; leachate recirculation; municipal solid waste; sanitary landfill; MUNICIPAL SOLID-WASTE; ANAEROBICALLY DECOMPOSED REFUSE; METHANE PRODUCTION; Engineering; Environmental Sciences & Ecology